A pact with happiness: intimate resistances in Eloy Sánchez Rosillo's last poetry - Cano Vidal, Borja (Tropelías: Review of Literary Theory and Comparative Literature, 2018)
The poetical voice of Eloy Sánchez Rosillo (Murcia, 1948) is considered to be one of the most singular and emphasized from the panorama of the Spanish contemporary poetry. From the publication of La certeza (2015), his aesthetics, till then tied to an elegiac and melancholy tone, experienced a draft in which the celebratory, the hymnic character and the singing to the fullness of the instant and of the present have turned into his more notable characteristics. This papers goes deeply, in relation whit this peculiarity, into the composition and expression of a poetics of happiness and in the principal axes that build it. This way, the summer recollection of his infancy and the different birds that them they him resemble, close to the element of the commonness, form the principal acts of intimate resistance in which the poet finds his principal handle to live in the immense instant that for him constitutes the present.
Keywords: Eloy Sánchez Rosillo; spanish contemporary poetry; happiness; intimacy; commonness